Smart watering system - Fitri, Umar Zainal; Asla, Muhamad Syamil Darwish; Nik Abu Bakar, Nik Ahmad Fahmi (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The Smart Watering System is an innovative IoT-based product designed to automate irrigation for small plants or gardens, offering convenience for individuals with busy lifestyles. This system uses Arduino IDE C++ programming to integrate a soil moisture sensor, humidity sensor, ESP8266 Wi-Fi module, and a water pump. Using the Blynk application, users can monitor and control the watering process remotely with a single touch, making plant care effortless and efficient. The system continuously monitors soil moisture levels and environmental humidity to determine optimal watering times. When soil moisture falls below a specified threshold, the water pump is activated automatically, ensuring plants receive the right amount of water without waste. The Blynk app allows users to customize thresholds, receive real-time notifications, and override the automation for manual control when needed. This project is tailored for urban gardeners, busy professionals, and small-scale plant enthusiasts who want to ensure their plants thrive without constant attention. By combining affordability, ease of use, and smart automation, this product addresses the growing demand for sustainable and user-friendly gardening solutions. The system is designed for scalability, making it adaptable for various plant types and garden sizes.